Skin Temperature in Parkinson’s Disease Measured by Infrared Thermography - Mathias Møller Purup; Karoline Knudsen; Pall Karlsson; Astrid Juhl Terkelsen; Per Borghammer (Parkinson's Disease)
Background. Patients with Parkinson’s disease (PD) often show peripheral autonomic dysfunction and depositions of pathological alpha-synuclein aggregates in the skin. However, functional consequences of this skin involvement have received little attention. Objective. To determine thermographic differences in the skin between healthy controls (HCs) and PD patients on hands, feet, and trunk and to correlate findings with symptoms and signs of dysautonomia. Between-group differences in autonomic parameters and questionnaires were explored. Methods. Twenty-one PD patients and 19 HCs were examined by thermographic infrared imaging of standardized anatomical locations on the trunk and upper and lower extremities at baseline and after exposure to cold stress test (CST). Thermal recovery rates (RRs) were determined on the basis of thermograms. Correlation analyses between alterations in skin temperature and autonomic dysfunction were performed. Results. The most significant RR difference between PD patients and HCs was seen on the fifth distal phalanx 10 minutes post-CST (mean RR ± SD: 51 ± 18% vs. 70 ± 23%, p = 0.003). No between-group differences were seen in baseline or post-CST values of the feet. No correlations were seen between thermal parameters and clinical and autonomic data. In the HC group, a positive, moderate correlation was seen between post-CST recovery values on the 3rd and 5th phalanx and body mass index (BMI) (r = 0.661, p = 0.002). Conclusions. The PD patients exhibited significant reduction in RR compared to HC and patients also displayed altered thermal responses in multiple anatomical locations. Thus, infrared thermography could become an important future tool in investigation of autonomic deficiency in PD.